Sepsis in a university hospital: a prospective study for the cost analysis of patients' hospitalization - Barreto,Maynara Fernanda Carvalho (2016)
Abstract OBJECTIVE To estimate the cost of hospitalization of patients with severe sepsis or septic shock admitted or diagnosed in the Urgent and Emergency sector at a university hospital and followed until the clinical outcome. METHOD An epidemiological, prospective, observational study conducted in a public hospital in southern Brazil for the period of one year (August 2013 to August 2014). Sepsis notification forms, medical records and data of the cost sector were used for the collection of clinical and epidemiological data. RESULTS The sample comprised 95 patients, resulting in a total high cost of hospitalization (R$ 3,692,421.00), and an average of R$ 38,867.60 per patient. Over half of the total value of the treatment of sepsis (R$ 2,215,773.50) was assigned to patients who progressed to death (59.0%). The higher costs were related to discharge, diagnosis of severe sepsis, the pulmonary focus of infection and the age group of up to 59 years. CONCLUSION The high cost of the treatment of sepsis justifies investments in training actions and institution of protocols that can direct preventive actions, and optimize diagnosis and treatment in infected and septic patients.